Invasive Species in Puerto Rico: The View From El Yunque - Zimmerman, Jess K.; Rojas-Sandoval, Julissa; Shiels, Aaron B. (Frontiers in Ecology and Evolution, 2021)
Native flora and fauna of Puerto Rico have a long biogeographic connection to South America. Theory and empirical evidence suggest that islands, particularly those distantly isolated from mainland, should be more susceptible to naturalizations and invasions of non-native species than continental areas. Anthropogenic disturbances can facilitate accidental and deliberate introductions of non-native species. In this study we asked: What is the current status of introduced non-native species within El Yunque National Forest (EYNF), the largest and most well-conserved forest area of Puerto Rico? and Does the biogeographic affinity of Puerto Rico to the Americas, and the levels of anthropogenic disturbance, help explain the patterns we see? To address these questions, we reviewed the literature and surveyed local experts to identify naturalized and invasive species of different plant and animal taxa occurring within EYNF. We found that there is only partial evidence that supports our hypothesis that well-conserved forest areas within EYNF are more resistant to invasion or occupation by non-native species than disturbed areas along roads or lowlands with a long history of human activity. This evidence is strongest in plants and birds. Otherwise, the more ubiquitous invasive species in EYNF include some mammals (feral cat, rat, and mongoose), and some invertebrates (earthworms, mosquito, and Africanized honeybee). For many taxa, there is little information to thoroughly test our hypothesis, and thus more detailed surveys of the status of non-native and invasive species in EYNF are needed.